The cabin at the end of the world : a novel - Tremblay, Paul (William Morrow, an imprint of HarperCollinsPublishers, 2018)
"The Bram Stoker Award-winning author of A Head Full of Ghosts gives a new twist to the home invasion horror story in a heart-palpitating novel of psychological suspense that recalls Stephen King's Misery, Ruth Ware's In a Dark, Dark Wood, and Jack Ketchum's cult hit The Girl Next Door"--